2020
DOI: 10.3389/fonc.2020.01031
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Aberrantly Methylated Differentially CpG Sites in Hepatocellular Carcinoma and Their Association With Patient Survival

Abstract: This study aimed to identify aberrantly methylated differentially methylated CpG sites (DMCs) and investigate their prognostic value in hepatocellular carcinoma (HCC). A total of 2,404 DMCs were selected from Gene Expression Omnibus (GEO) and validated by The Cancer Genome Atlas (TCGA). The TCGA cohort was divided into a training cohort and a validating cohort. First, the prognostic model based on six DMCs, including cg08351331, cg02910574, cg09947274, cg17589341, cg24652919, and cg26545968, was constructed ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
(59 reference statements)
1
0
0
Order By: Relevance
“…11 53 Thus, we developed a novel qPCR-based QASM assay 26 that has been shown validity in determining single-CpG methylation by an independent group. 54 In the current study, we also showed its validity in measuring the methylation level of each CpG included in the CD8+ MeTIL score. Compared with EPIC methylation array and pyrosequencing, the QASM assay is reliable to determine the CD8+ MeTIL score.…”
Section: Discussionsupporting
confidence: 57%
“…11 53 Thus, we developed a novel qPCR-based QASM assay 26 that has been shown validity in determining single-CpG methylation by an independent group. 54 In the current study, we also showed its validity in measuring the methylation level of each CpG included in the CD8+ MeTIL score. Compared with EPIC methylation array and pyrosequencing, the QASM assay is reliable to determine the CD8+ MeTIL score.…”
Section: Discussionsupporting
confidence: 57%